Dinamika Pengembangan Kurikulum Pendidikan Agama Islam pada Jenjang Raudhatul Athfal di Era Transformasi Digital - Titarini; Afifatus Soleha; Nanang Budianto; Faroha Amalia Husna (PT. Hasba Edukasi Mandiri, 2026)
The rapid development of information technology has brought significant changes across various aspects of life, including the field of Islamic religious education. These changes require a reorganization of the principles and factors influencing the development of the Islamic Religious Education curriculum, so that it remains aligned with contemporary developments while still prioritizing moral, spiritual values, and character formation. Studies on the development of the Islamic Religious Education curriculum at the Raudhatul Athfal level have so far been limited and tend to be normative or technical in nature. This study aims to analyze the dynamics of the principles and factors influencing the development of the Islamic Religious Education curriculum at the Raudhatul Athfal level in the era of digital transformation. This research employs a qualitative approach with a conceptual analysis design through literature study and theoretical synthesis. The results show that the development of the Islamic Religious Education curriculum at the Raudhatul Athfal level continues to evolve dynamically while remaining relevant, flexible, adaptive, and capable of integrating values and technology. Internal and external factors are interrelated in shaping the direction of curriculum development. This study produces an integrative-spiritual dynamic model of the Islamic Religious Education curriculum at the Raudhatul Athfal level, which expands classical curriculum development into a digital-based Islamic education framework. This model is expected to serve as a theoretical and practical reference in designing an Islamic Religious Education curriculum at the Raudhatul Athfal level that is in line with current developments without losing its spiritual foundation.